Chimeric antigen receptor-redirected T cells display multifunctional capacity and enhanced tumor-specific cytokine secretion upon secondary ligation of chimeric receptor. (June 2013) - Henderson, Melissa A; Yong, Carmen SM; Duong, Connie PM; Davenport, Alexander J; John, Liza B; Devaud, Christel; Neeson, Paul; Westwood, Jennifer A; Darcy, Phillip K; Kershaw, Michael H
Aim: The aim of the current study was to fully elucidate the functions of T cells genetically modified with an erbB2-specific chimeric antigen receptor (CAR).Material & methods: In this study, key functional parameters of CAR T cells were examined following antigen-specific stimulation of the chimeric anti-erbB2 receptor.Results: Gene-modified T cells produced the cytokines IFN-γ, IL-2, IL-4, IL-10, TNF-α and IL-17, and the chemokine RANTES upon CAR ligation. A multifunctional capacity of these CAR T cells was also demonstrated, where 13.7% of cells were found to simultaneously express IFN-γ and CD107a, indicative of cytolytic granule release. In addition, the CAR T cells were able to respond to a greater degree on the second ligation of CAR, which has not been previously shown. IFN-γ secretion levels were significantly higher on second ligation than those secreted following initial ligation. CAR-expressing T cells were also demonstrated to lyze erbB2-expressing tumor cells in the absence of activity against bystander cells not expressing the erbB2 antigen, thereby demonstrating exquisite specificity.Conclusion: This study demonstrates the specificity of CAR gene-engineered T cells and their capacity to deliver a wide range of functions against tumor cells with an enhanced response capability after initial receptor engagement.